2016
DOI: 10.1111/ajo.12521
|View full text |Cite
|
Sign up to set email alerts
|

Impact of type 2 diabetes, obesity and glycaemic control on pregnancy outcomes

Abstract: Despite availability of preconception care, good glycaemic control and specialist management, T2D remains associated with increased adverse obstetric and neonatal outcomes. Further research to examine predictors of adverse outcomes may assist in targeted antenatal surveillance and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 23 publications
1
45
0
1
Order By: Relevance
“…A fasting BG (FBG) target <5.9 mmol/L is still associated with a 29% macrosomia rate (74,80,81). Recent retrospective data demonstrated that a mean A1C ≥6.0% in pregnant women with type 2 diabetes was associated with increased risk of neonatal complications (preterm birth, neonatal intensive care unit [NICU] admission, neonatal hypoglycemia and jaundice) compared to women with an A1C <6.0% (82). In women with type 1 diabetes and good glycemic control during pregnancy with an A1C of 4.5% to 7.0%, there is still a linear relationship between third trimester A1C and risk of macrosomia (83).…”
Section: Targets Of Glycemic Controlmentioning
confidence: 99%
“…A fasting BG (FBG) target <5.9 mmol/L is still associated with a 29% macrosomia rate (74,80,81). Recent retrospective data demonstrated that a mean A1C ≥6.0% in pregnant women with type 2 diabetes was associated with increased risk of neonatal complications (preterm birth, neonatal intensive care unit [NICU] admission, neonatal hypoglycemia and jaundice) compared to women with an A1C <6.0% (82). In women with type 1 diabetes and good glycemic control during pregnancy with an A1C of 4.5% to 7.0%, there is still a linear relationship between third trimester A1C and risk of macrosomia (83).…”
Section: Targets Of Glycemic Controlmentioning
confidence: 99%
“… Abell, Abell and Shand report on pregnancies ending at 20 or more weeks, or with birthweight 400 g minimum if gestational ageis not known. McElduff's Research Letter does not define perinatal mortality but compares findings with NSW Midwives Database 2002 which uses the same criteria as the previous three studies . Wong, Gunton and Kothari do not define perinatal mortality by gestational age or birthweight. No studies define the greatest infant age up to which death contributes to perinatal mortality, but most imply that data collection is limited to neonatal inpatient death. In addition to reporting all‐cause perinatal mortality as tabulated above, Abell and Kothari report perinatal mortality in the absence of detected congenital malformation. …”
Section: Methodsmentioning
confidence: 82%
“…Internationally, nulliparous women comprised between 16.4% and 67.0% of women with PPDM. Australian studies report between ⅓ and ½ of women with PPDM are nulliparous (see Table and Fig. ), similar to 45% nulliparity among unselected mothers…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations